Schwannoma in the Supraclavicular Region: Case Report - Keleş, Erol (Turk Arch Otorhinolaryngol, 2018)
Schwannomas are benign tumors arising from schwann cells in peripheral, cranial, and autonomic nerve sheaths. Approximately half of all cases of schwannomas are observed in the head and neck region. In this study, a 71-year-old male patient presenting with a stiff mobile mass in the left supraclavicular region and diagnosed as a schwannoma after total excision was presented.